Another use for a proven drug: experimental evidence for the potential of artemisinin and its derivatives to treat Alzheimer's disease - Kiss, Eva; Kins, Stefan; Gorgas, Karin; Venczel Szakács, Kinga Hajnal; Kirsch, Joachim; Kuhse, Jochen (International journal of molecular sciences, 2024)
Plant-derived multitarget compounds may represent a promising therapeutic strategy for multifactorial diseases, such as Alzheimer's disease (AD). Artemisinin and its derivatives were indicated to beneficially modulate various aspects of AD pathology in different AD animal models through the regulation of a wide range of different cellular processes, such as energy homeostasis, apoptosis, proliferation and inflammatory pathways. In this review, we aimed to provide an up-to-date overview of the experimental evidence documenting the neuroprotective activities of artemi-sinins to underscore the potential of these already-approved drugs for treating AD also in humans and propose their consideration for carefully designed clinical trials. In particular, the benefits to the main pathological hallmarks and events in the pathological cascade throughout AD development in different animal models of AD are summarized. Moreover, dose- and context-dependent effects of artemisinins are noted.
Gesehen am 18.03.2025